Accounting for Revaluation of Property, Plant and Equipment in 2017 and 2020: New in the Draft Federal Accounting Standard “Property, Plant and Equipment” - Aleksei Evgen’evich Ivanov; Ol’ga Gennad’evna Nikitina (Учёт. Анализ. Аудит)
Introduction, Purpose. The article deals with the accounting for revaluation of property, plant and equipment. There are two accounting procedures for that: the current one running in 2017, and the one to be introduced in 2020. The article aims to acquaint the professional community with the pending changes in the Russian accounting regulatory system. Methods. In the study, we used methods of analysis, synthesis, comparison, generalization, analogy, and the ascent from the abstract to the concrete. The Russian Accounting Standards, International Financial Reporting Standards, and the Draft Federal Accounting Standard “Property, Plant and Equipment” are the research source data. Results. We made the analysis of the accounting for revaluation of property, plant and equipment in accordance with: 1) Russian Ministry of Finance’s regulatory documents, which are operating in 2017; 2) Draft Federal Accounting Standard “Property, Plant and Equipment”. We revealed the discrepancies between actual accounting rules for revaluation of property, plant and equipment and the ones planned for introduction. We provided an example of the accounting for revaluation of property, plant and equipment in accordance with the Draft Federal Accounting Standard “Property, Plant and Equipment”. Discussion. The accounting procedure for revaluation of property, plant and equipment proposed in the Draft Federal Accounting Standard “Property, Plant and Equipment” complicates to some extent the domestic methodology of accounting for fixed assets as this procedure assumes variability of the methods used and using the accountant’s professional judgment in choosing them. The results of the research could be used in further discussion of the Draft Federal Accounting Standard “Property, Plant and Equipment” and in training accounting practitioners and instructors in the medium tеrm.